ANALISIS PERHITUNGAN METODE COST PLUS PRICING DALAM MENENTUKAN HARGA JUAL RUMAH PADA PT. PURNI MEKAR PERKASA JAYA - Rudi Hermanto; Subagyo Subagyo; Mas Wibowo Andoko (POLITEKNIK CAHAYA SURYA, 2018)
This study aims to determine the calculation of the cost plus pricing method in determining the selling price of houses at PT. Purni Mekar Perkasa Jaya. So that it is expected that the results of this study can contribute to the company and become a consideration especially in taking policy. Data analysis techniques in this study using Quantitative Descriptive Analysis. The object of this research is PT. Purni Mekar Perkasa Jaya is engaged in housing developers.The results of this study indicate the calculation of the cost plus pricing method in determining the selling price of a house at PT. Purni Mekar Perkasa Jaya experienced a difference in the difference from the calculation of the company method. Due to the difference in costing from the start and some costs that are not taken into account in the preparation of the cost of production, namely office costs and building depreciation costs. Determination of selling prices that are less comprehensive and result in some costs that have not been included in determining the selling price, namely sales fees and general and administrative costs. Keywords: Cost Plus Pricing, House Selling Prices.